Evolving classification and role of muscle biopsy in diagnosis of inflammatory myopathies - Meenakshi Swain; Megha Uppin (Wolters Kluwer Medknow Publications, 2022)
Idiopathic inflammatory myopathy (IIM) is a broad term that includes dermatomyositis, polymyositis, overlap myositis, sporadic inclusion body myositis, and immune-mediated necrotizing myopathy. The understanding of the pathogenesis of IIM is ever-evolving with regular updates in the classification schema. With the recognition of autoantibodies and their detection, the diagnostic algorithms are changing in favor of non-invasive diagnoses. However, muscle biopsy has immensely contributed to our understanding of the pathogenesis of inflammatory myopathies, and the pathologic features of different subtypes are well established. The biopsy also aids in distinguishing myopathies with overlapping clinical features, particularly dystrophies, which can show inflammation on biopsy in some cases. In this article, the various classification schemes of the IIM are reviewed. Also, the pathogenesis and pathology of each type of IIM have been highlighted. This article emphasizes the role of muscle biopsy in the diagnosis of inflammatory myopathies.